Person and Self-Value - Scheler, Max. author. aut Link
XXIX, 201 p.
Keywords: From the mysterious powers and forces peculiar to both individual and community that can turn our lives into either good or bad lives, I wish to point to two such powers being at the same time different in their own nature and yet closely related to each other: The powers that emerge from exemplary persons and leaders. Understood as basic to both sociology and the philosophy of history, it comes to us as no surprise that the problem of exemplary persons and leaders - along with the questions of the qualities types, selections and education of leaders; forms of unison existing be tween leaders and their followers, all of which belonging to the subdivisions of this problem - must be a burning problem for a people whose historical leaders from all walks of life have, in part, been swept away by wars and revolutions. This fact we also find in all salient epochs of history characterized more or less by changes in leadership. It is precisely for this reason that in our own time every group appears to struggle ever so hard with this problem, namely, who their leaders should be. This pertains equally to a group within a party, to a class, to occupations, to unions, to various schools or present-day youth movements, and even to religious and ecclesias tical groupings. Beyond any comparison, there is yearning everywhere for lead ership.